The stability of enzymes after sonication - Özbek, B; Ülgen, KÖ (ELSEVIER SCI LTD, 2000)
The effects of operating conditions of sonication on the stability of some commercially purified enzyme preparations were investigated. Buffered solutions of six enzymes, alcohol dehydrogenase (ADH), malate dehydrogenase (MDH), glucose-6-phosphate dehydrogenase (G6PDH), L-lactic dehydrogenase (LDH), alkaline phosphatase (AP) and beta-galactosidase (beta G)were sonified over a range of power outputs up to 40 W. The enzymes had variable stabilities with complete stability for AP, and over 70% inactivation for G6PDH. Some inactivation models were tested for an understanding of the relation between sonification intensity and enzyme stability. Sonication processing times also affected the inactivation rate of ADH and MDH. The stability of sonified ADH was decreased with time when compared with unsonified controls. Increasing the viscosity of process fluid with glycerol gave 39% inactivation of ADH, while the control showed 15% inactivation for the operational conditions. The forces involved in the fluid must therefore have a significant role to play in the inactivation process. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: enzyme stability; inactivation; acoustic cavitation; wave duty cycle; ALCOHOL-DEHYDROGENASE; RELEASE KINETICS; CELL DISRUPTION; SHEAR; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering